Majas dalam Lirik Lagu Album Top Hits Elly Kasim Volume 2 - Wahyuni, Helmi Fitri; Semi, M. Atar; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purposes of this study were (1) describe the kind of figure of speech that contained in the lyrics of the song in Elly Kasim’s Top Hits Volume album 2. (2) describe the function of figure of speech in the lyrics of the song in Elly Kasim’s  Top Hits Volume 2 album. The data of research are the lyrics of songs in the album Top Hits 1960-1970 Volume 2 Elly Kasim. Sources of the research data are the songs in the cassette album Top Hits 1960-1970 Volume 2, produced by Elly Kasim S. Suryaman Group. Album Top Hits Volume 2 1960-1970 Elly Kasim consist of 18 song titles. Data were collected with eight techniques. 1) Play the cassette tape album Top Hits 1960-1970 Volume 2 by Elly Kasim and listen the lyrics of the song playing. 2) Take note of the lyrics of the song that you listen. 3) Read all of the lyrics of the song, 4) Marking figure of speech using words in the song lyrics, 7) Deciphering the lyrics into Indonesian. 6) Determine the theme and the message of song 7) inventory figure of speech contained in the lyrics of the song, 8) Interpreting the function of figure of speech. The result of the study that found 13 kinds of figure of speech of 18 song titles, there are 5 kinds of  theme and the message of the 18 song titles and functions of each figure of speech.